2021
DOI: 10.3389/ijph.2021.1604149
|View full text |Cite
|
Sign up to set email alerts
|

What Influences the Sustainable Food Consumption Behaviours of University Students? A Systematic Review

Abstract: Objectives: Global environmental challenges demand sustainable behaviours and policies to protect human and planetary health. We aimed to summarize the evidence about the factors related to Sustainable Food Consumption (SFC) behaviours of university students, and to propose an operational categorization of SFC behaviours.Methods: Seven databases were searched for observational studies evaluating Sustainable Food Consumption (SFC) among university students and that reported at least one behavioural outcome meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 81 publications
1
16
1
Order By: Relevance
“…In previous research, younger, well-educated individuals have demonstrated better knowledge of aspects related to sustainability [10], and increasing educational attainment is consistently associated with sustainable food choices [12]. Sustainable food choices in this group have been shown to be influenced by friends, family and information resources including documentary films, books and university courses [13].…”
Section: University Students Perceptions Of Sustainable Foodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous research, younger, well-educated individuals have demonstrated better knowledge of aspects related to sustainability [10], and increasing educational attainment is consistently associated with sustainable food choices [12]. Sustainable food choices in this group have been shown to be influenced by friends, family and information resources including documentary films, books and university courses [13].…”
Section: University Students Perceptions Of Sustainable Foodsmentioning
confidence: 99%
“…A recent systematic review identified a small group of studies, of varying quality, that investigated sustainable food behaviors and purchasing patterns in university student populations internationally, showing the consumption of seasonal and local foods was the main behavior used towards sustainable food consumption in this group [12]. The proportion of students consuming sustainable foods also varied by study [12]. However, the review highlighted that research in the Australian context was scant.…”
Section: University Students Behaviors Towards Purchasing Sustainable Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Restricting the merchandising of discretionary food and beverages in retail settings (Australia) 121 Barriers and facilitators for creating healthy food retail outlets – perspectives from Australian local government authorities (Australia) 122 Applying the ecological determinants of health perspective to reconsider the current retail foodscape (United States of America and Canada) 123 A systematic review of factors influencing sustainable food consumption behaviours amongst university students, examining the effects of choice architecture interventions (International) 124 …”
Section: Resultsmentioning
confidence: 99%
“…• Restricting the merchandising of discretionary food and beverages in retail settings (Australia) 124 (Continues)…”
Section: Setting Policymentioning
confidence: 99%